Frequency of radix molaris in mandibular first and second molars using cone-beam computed tomography images in a selected Iranian population - Mehrad Rafiei; Zahra Tafakhori (Babol University of Medical Sciences, 2022)
Introduction: Adequate knowledge of dental anatomy is essential for successful endodontic treatment. The aim of this study was to determine the frequency of radix molaris in permanent mandibular first and second molars using cone-beam computed tomography (CBCT) in Rafsanjan-Iran in 2020. Materials & Methods: The present study was conducted on CBCT images taken at a private oral and maxillofacial radiology clinic in Rafsanjan, Iran, in 2020. A total of 407 teeth were examined. An experienced radiologist reconstructed and examined the images in axial and, if necessary, sagittal section. Finally, the data were entered into SPSS 22 and analyzed using the chi-square test. A value of P<0.05 was considered statistically significant.  Results: A total of 365(89.8) teeth, including 156 first molars and 209 second molars, were included in the study. Of these, 212 (58.1%) belonged to females and 153 (41.9%) to males. Sixteen (4.4%) teeth had three roots, all of which were first molars. Moreover, the extra roots were on the distolingual side and were radix entomolaris in all 16 cases. The prevalence of radix molaris was significantly higher in first molars (P=0.001) but did not differ by tooth side or sex. Conclusion: The three-rooted mandibular first molars may occur in the Iranian population and are not a rare phenomenon.